ANALISIS TANGGUNG JAWAB PEJABAT LELANG KELAS I ATAS KESALAHAN REDAKSIONAL RISALAH LELANG TERKAIT EKSEKUSI HAK TANGGUNGAN MELALUI PERMOHONAN KEPADA KETUA PENGADILAN (STUDI KASUS: PENETAPAN NOMOR 02/EKS.HT/2018/PN.SNT)ANALISIS TANGGUNG JAWAB PEJABAT LELANG KELAS I ATAS KESALAHAN REDAKSIONAL RISALAH LELANG TERKAIT EKSEKUSI HAK TANGGUNGAN MELALUI PERMOHONAN KEPADA KETUA PENGADILAN (STUDI KASUS: PENETAPAN NOMOR 02/EKS.HT/2018/PN.SNT) - Lavetta Ferels; Gunawan Djajaputra (Jurnal Hukum Adigama, 2021)
Determination Number 02/Eks.HT/2018/PN.SNT, granted the request for revocation of execution. Excerpt from the Minutes of Auction number: 203/2013 describes the auction object that was sold but there is an editorial error regarding the PLTU Turbine, it should be the PLTU Turbine Building. What is the Class I Auction Officer's responsibility for editorial errors in the Auction Minutes? What legal remedies can a third party take for the editorial error of the Minutes of Auction?. The problems were analyzed comprehensively by using normative juridical law research methods. Each auction must be preceded by an announcement of the auction, then Minutes of Auction are made by the Auction Officer. The buyer receives a Minutes of Auction Quotation as a Deed of Sale and Purchase. Correction of editorial errors after the Auction Minutes is closed and signed may not be carried out, unless there is a principal editorial error related to the legality of the subject and object of the auction which can harm the seller and/or buyer if no correction is made, or becomes a finding of the Superintendent or the functional examiner and needs to be followed up. with correction. Correction of editorial errors as stated in the Minutes of Written Warning is the lowest level of sanctions that can be given to the Auction Officer in the event of an editorial error in the minutes of the auction. Article 40 of the Regulations for Selling in Public in Indonesia (Ordinance 28 February 1908, S. 1908-189, effective from 1 April 1908 states that the auctioneer is responsible for all losses arising from non-compliance with the provisions of articles 37, 38, and 39 above. Where in articles 37, 38 and 39 basically describe the minutes of the auction.